PERBANDINGAN REGULASI PERLINDUNGAN DATA PRIBADI ANTARA INDONESIA DAN SINGAPURA DALAM KONTEKS KASUS WORLDCOIN - Alfaaiz, Mohamad Gery (JOURNAL EQUITABLE, 2025)
This study examines the comparative regulation of personal data protection between Indonesia and Singapore in the context of the Worldcoin case, a global project collecting biometric data through iris scanning. The central research question concerns the differences in legal frameworks for protecting biometric data and their implications for citizen protection. This research adopts a normative legal method with a comparative and case study approach. The findings reveal that Indonesia’s Law No. 27 of 2022 on Personal Data Protection explicitly classifies biometric data as specific personal data requiring explicit consent. However, Indonesia lacks a dedicated supervisory authority and has limited technical regulation concerning specific biometric types such as iris scans. On the other hand, Singapore’s Personal Data Protection Act (PDPA) provides a principle-based framework that offers flexibility regarding consent and accountability, supported by an active supervisory body (PDPC). These differing approaches influence how each country responds to the Worldcoin initiative: Singapore opted for regulatory audits, while Indonesia suspended activities based on administrative discretion. The study recommends strengthening institutional oversight and enhancing Indonesia’s technical regulation to address biometric technologies more effectively and adaptively.